Efektivitas Ekstrakurikuler Kepramukaan Dalam Pembentukan Kepribadian Peserta Didik di Mi Sultan Agung Watukelir Kecamatan Ayah Kabupaten Kebumen - Setianingrum, Mey Nanda; Maesaroh, Maesaroh (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The purpose of this research is (1) to find out how effective scouting extracurriculars are in forming the personality of students at MI Sultan Agung Watukelir (2) to find out how extracurricular scouting methods are in forming the personality of students at MI Sultan Agung Watukelir (3) to find out what extracurricular obstacles are scouting in forming the personality of students at MI Sultan Agung Watukelir (4) to find out how extracurricular scouting results in forming the personality of students at MI Sultan Agung Watukelir. This type of research uses descriptive qualitative research, with a description of the problem that is in accordance with the facts in the field. The subjects in the research included the Head of Madrasah MI Sultan Agung Watukelir, scout leaders, homeroom teachers from grades 1 to grade 6, several students from grades 4, 5 and 6 totaling 5 students. This research uses data collection techniques based on observation, interviews and documentation with data analysis in the form of data reduction, data presentation and drawing conclusions. Based on the research results, it was concluded that: (1) Scouting extracurricular activities in shaping the personality of students at MI Sultan Agung Watukelir, Ayah District, Kebumen Regency have been declared effective. This is obtained from the results of the description of effectiveness, namely accuracy of targets, implementation and monitoring of the program (2) the formation of personality in students, including obedience, discipline, responsibility, politeness, as well as maintaining and protecting the natural environment. This cannot be separated from the existence of scout activity plans that are in accordance with the Basic Principles of Scouting and Scouting Methods. MI Sultan Agung Watukelir has implemented several scouting methods in accordance with the AD ART of the Scout Movement (3) There are several obstacles in implementing scout activities at MI Sultan Agung Watukelir, including the low interest of some students in taking part in scout extracurricular activities at the madrasah, the lack of a special room to store scout equipment and the low level of collaboration between teachers due to the busyness of each teacher so that there is no can help develop and accompany the running of scout activities.